Spatiotemporal analysis of rainfall variability using satellite precipitation in watersheds - M.D. Syaifullah; A. Purwandani; M. Kudsy; Tukiyat ,; S. Tikno; A.E. Sakya; F.H. Widodo; S. Bahri; Muktiyono , (Global Journal of Environmental Science and Management, 2025)
BACKGROUND AND OBJECTIVES: Understanding spatial and temporal rainfall variability is essential for effective water resource management in Indonesia, where diverse landscapes and dynamic tropical climates cause uneven precipitation that often leads to localized floods or droughts. This study aims to investigate how geomorphological and topographical differences across the Toba-Asahan, Brantas, and Larona-Malili watersheds in Indonesia influence rainfall distribution and trends, in order to support adaptive and sustainable watershed management.METHODS: This study analyzes rainfall variability in three distinct Indonesian watersheds, Toba-Asahan, Brantas, and Larona-Malili, using climate hazards group infrared precipitation with Station version 2 satellite precipitation data. The spatial and temporal patterns of rainfall are examined in relation to each watershed’s unique geomorphological and topographical characteristics. Basic statistical analysis and mapping techniques are used to identify trends and visualize distribution patterns, aiming to provide insights into how natural landscape features influence rainfall behavior and water availability at the watershed scale.FINDINGS: The results reveal a significant long-term increase in rainfall in the Larona-Malili watershed, while no statistically significant trends are observed in the Brantas and Toba-Asahan watersheds. The dominant rainfall patterns reflect the unique regional climatic characteristics of each watershed. Spectral analysis highlights the influence of El Niño Southern Oscillation and Indian Ocean Dipole, showing semi-annual rainfall patterns in Toba-Asahan and Larona-Malili, and an annual cycle in Brantas. Climatic sensitivity differs across the three watersheds, as reflected by the varying influence of the Webster-Yang Monsoon Index, El Niño Southern Oscillation, and Indian Ocean Dipole.CONCLUSION: This study comprehensively analyzes rainfall variability in three significant watersheds in Indonesia; the Brantas, the Toba-Asahan, and the Larona-Malili watersheds. Another finding from this study is that seasonal rainfall patterns in the Brantas watershed is significantly influenced by the Asian Monsoon. In contrast, the Toba-Asahan and Larona-Malili watersheds are shaped by local and regional factors, with land use changes playing a role in rainfall variability and water resource impacts. Annual patterns vary among the watershed, with Toba-Asahan experiencing year-round rainfall peaking from August to December, Brantas dominated by afternoon convection-driven rain from January to April and November to December, and Larona-Malili showing morning-to-noon rainfall from May to July due to local circulation and topographic effects. The findings provide valuable insights into managing water resources and addressing climate change and extreme weather variability in Indonesia. In conclusion, the overall results of this study may serve as a basis for water resource management in the three watersheds, especially in the face of potential climate change and extreme weather variability.